Pengaruh Belanja Modal Dan Investasi Swasta Terhadap Penyerapan Tenaga Kerja Kabupaten/Kota Di Provinsi Kalimantan Barat Tahun 2009-2013 - B01111064, Rika Aria Dwi B01111064 Aria Dw (Jurnal Pembangunan dan Pemerataan, 2015)
Going to call this research is the influence of capital expenditure and private investment to employment districts in West Kalimantan Province years 2009-2013. This study aims to analyze the influence of capital expenditure and private investment to employment districts in West Kalimantan Province years 2009-2013. This research uses the method explanatory research with use the model regression multiple and the means of statistical analysis that is the determination (R2), the F-statistic, and the T statistic to know hypothesis do capital expenditure and private investment impact on employment, the data used was data panel. This research result indicates that capital spending it has some positive effect of 0,000333 and significant, while private investment it has some positive effects of 0,015847 and insignificant to employment districts in West Kalimantan Province. Value the coefficients determination of 0,764695 which means the size of influence exerted by variabel capital expenditure and West Kalimantan Province of 76%, while the rest of 24% influenced by other factors such as wages, government policy and technology. Â  Keywords: Capital Expenditure, Private Invesment, Employment Districts